Essays on government - "Barker, Ernest" (Oxfrod, 1965)
This book is deal with British Monarch, having a collection of seven essays. The first four essays, which deal with matters of modern government in Great Britain and France, have all been written, though on different occasions and for different purposes, since the spring of I94I. The first two essays are concerned with British kingship and British statesmanship. The third is an essay on parliamentary government-mainly in Britain and France-which was intended to serve both French and English readers and appeared originally both in an English and a French version. The fourth essay was intended to give a summary account of the government of the Third Republic for the benefit of English readers. The original draft has been revised and enlarged; and the author hopes that the essay may, in its present form, help English readers to sympathize with the difficulties of the Third Republic, and-even more-to admire the height of its achievement, particularly in the domains of legislation and justice. The next three essays-the fifth, sixth, and seventh-are concerned with the history of political ideas in England during the second half of the eighteenth century. This was a period on which the author regularly lectured, for some years, during his tenure of the Chair of Political Science in Cambridge. The essay on Blackstone's account of the British Constitution was written, in its present form, as recently as the spring of I943
Keywords: Political Science